PENGARUH TANGGUNGJAWAB SOSIAL PERUSAHAAN TERHADAP PROFITABILITAS DENGAN VARIABEL MODERASI TATA KELOLA PERUSAHAAN - Cristy Putra, Stephanus Himawan; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to study the influence of corporate social responsibility (CSR) to the profitability (ROE) with the Good Corporate Governance (GCG) as the moderating variable in the manufacturing company in the food and beverages companies which are listed in the IDX in 2012-2014 periods. The samples are 13 food and beverages companies which are listed in the IDX, with the observation numbers are 39 and they have been selected by using purposive sampling. The data of audited financial statement and annual statement have been obtained from Indo-Exchange File (IDX). The hypothesis test has been done by using multiple linear regressions to test the influence of corporate social responsibility (CSR) in profitability (ROE) with the Good Corporate Governance (GCG) as the moderating variable. In this research the corporate social responsibility variable (CSR) is measured by using the corporate social disclosure index (CSDI) variable, profitability is measured by using return on equity (ROE), and the Good Corporate Governance (GCG) has been done by using management ownership. The result of this research which has been done by using multiple linear regressions shows that corporate social responsibility (CSR) has an influence to the profitability (ROE). Meanwhile, the analysis of moderating variable with method of interaction test which is moderated regression analysis (MRA) shows that the Good Corporate Governance is moderated the influence of corporate social responsibility (CSR) in profitability (ROE).Keywords: Corporate Social Responsibility, Profitability, Good Corporate Governance (GCG).